Nanocellulose: Recent advances and its prospects in environmental remediation - Shak, Katrina Pui Yee; Pang, Yean Ling; Mah, Shee Keat (Beilstein Journal of Nanotechnology, 2018)
Among many other sustainable functional nanomaterials, nanocellulose is drawing increasing interest for use in environmental remediation technologies due to its numerous unique properties and functionalities. Nanocellulose is usually derived from the disintegration of naturally occurring polymers or produced by the action of bacteria. In this review, some invigorating perspectives on the challenges, future direction, and updates on the most relevant uses of nanocellulose in environmental remediation are discussed. The reported applications and properties of nanocellulose as an adsorbent, photocatalyst, flocculant, and membrane are reviewed in particular. However, additional effort will be required to implement and commercialize nanocellulose as a viable nanomaterial for remediation technologies. In this regard, the main challenges and limitations in working with nanocellulose-based materials are identified in an effort to improve the development and efficient use of nanocellulose in environmental remediation.
Keywords: adsorbent; environmental remediation; membrane; nanocellulose; nanomaterials; photocatalyst